MAGNETIC ANISOTROPY OF ANDESITIC ROCKS FROM THE ISLAND OF JAVA - (NIM: 30203003), KHUMAEDI
This experimental based research was objectived to conceive the cause of magnetic anisotropy of the andesitic igneous rock based on empirical measurement. Anisotropy is physical different response of material to orientation measurement applied. The magnetic anisotropy of igneous rock was mainly controlled by magnetic minerals on it. Besides, the study of the contribution of magnetic minerals and other minerals to the magnetic anisotropy in igneous rocks is rarely. Therefore, we concern to study on existence of magnetic minerals in igneous rocks, especially the andesitic rocks. The existence of magnetic minerals was related to the condition of the mineral it self, such as phase of mineralogy, magnetic grain size, abundance of elemental composition and position to another nonmagnetic minerals. By doing this study we were expected to make an explanation about the existence of magnetic anisotropy in the andesitic rocks. The samples in this research are the extrusive and intrusive andesitic rock. Those samples were cut from 21 sites that are distributed all the way from West to East Java. The parameters measured are magnetic susceptibility, anhysteretic susceptibility, phase mineralogy, magnetic grain size and elemental composition of andesitic rocks. In this study, heating treatment gradually also done to explore the characteristic of magnetic anisotropy parameters after heating treatment. From the result, we can conclude that magnetic anisotropy of the andesitic rocks is caused by the distribution of the magnetic minerals which are not distributed on the whole igneous matrix. It is the effect of the formation process of igneous rocks. The variety process of the formation would made the variety of the magnetic grain size, the elemental composition and the magnetic anisotropy. The heating treatment would also altered the magnetic anisotropy of the igneous rocks.